2019
DOI: 10.1177/1750481319893769
|View full text |Cite
|
Sign up to set email alerts
|

Discursive construction of Syrian refugees in shaping international public opinion: Turkey’s public diplomacy efforts

Abstract: This research focuses on the Turkish government’s communications with the international community with regard to Syrian refugees. I use the Discourse Historical Approach to reveal and compare the discursive strategies that the official Turkish news agency has used as part of its public diplomacy efforts in their mass communication efforts regarding Syrian refugees during the last 8 years. The results reveal how a humanitarian issue such as the plight of refugees might be employed to establish a government’s po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Other studies focus on the way refugees are represented and how the reality of the human beings portrayed is renegotiated through the different multimodal resources (Mielczarek, 2020;Mustafa-Awad and Kirner-Ludwig, 2021;Özdora Akşak, 2019). These studies reinforce the rhetorical powers of images and their importance in influencing the audience's ideology while associating refugees with humanitarianism, conflict, dehumanization, security, economic burden, political responsibility and integration, among others.…”
Section: Multimodalitymentioning
confidence: 96%
“…Other studies focus on the way refugees are represented and how the reality of the human beings portrayed is renegotiated through the different multimodal resources (Mielczarek, 2020;Mustafa-Awad and Kirner-Ludwig, 2021;Özdora Akşak, 2019). These studies reinforce the rhetorical powers of images and their importance in influencing the audience's ideology while associating refugees with humanitarianism, conflict, dehumanization, security, economic burden, political responsibility and integration, among others.…”
Section: Multimodalitymentioning
confidence: 96%
“…Efe, 2019) or to specific points in time: for example, with respect to the ‘European refugee crisis’, Chouliaraki et al (2017) report that comparatively short periods of ‘cautious tolerance’ and ‘ecstatic humanitarianism’ preceded the subsequent – and much more stable – trend to demonise MENA refugees. One exceptional study has not found any evidence of discourse of threat based on an analysis of news published in Turkey’s ‘official news outlet’ Anadolu Agency (Akşak, 2020). Instead, it has shown that Anadolu Agency construed ‘Turkey as the saviour of the Syrian people, treating refugees fairly from a humanitarian perspective and offering context for their plight by providing human interest stories that show their victimisation’ (Akşak, 2020: 309).…”
Section: Introductionmentioning
confidence: 99%
“…One exceptional study has not found any evidence of discourse of threat based on an analysis of news published in Turkey’s ‘official news outlet’ Anadolu Agency (Akşak, 2020). Instead, it has shown that Anadolu Agency construed ‘Turkey as the saviour of the Syrian people, treating refugees fairly from a humanitarian perspective and offering context for their plight by providing human interest stories that show their victimisation’ (Akşak, 2020: 309). Nonetheless, the author suggests that this favourable portrayal served the opportunistic political goal of establishing or strengthening the Turkish government’s position on the international arena.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining the identity of the group of ethnic minorities, immigrants, asylum seekers, and refugees in discourse genre such as media discourse and political discourse include Van Dijk (1993a, 2000, Baker and McEnery (2005), Clyne (2005), Baker (2006, 2008), KhosraviNik (2010), Menjívar, Ruiz, and Ness (2019). The Syrian refugees' portrayal in the media and politico-economic discourse has been covered in studies such as Ulum (2016), Abid, Manan and Rahman, (2017), Aslan (2017), Arcimaviciene and Baglama (2018), Bhatia and Jenks (2018), Efe (2019), Gulmez (2019), Onay-Coker (2019), Romano (2019), Akşak (2020), Zibin (2020), Mustafa-Awad and Kirner-Ludwig (2021), and Dolores Porto (2022). The main ndings in these studies are that the Syrian refugees are the cause of internal struggle and threat especially to the countries hosting them.…”
Section: Introductionmentioning
confidence: 99%